Effect of Sulphur and Bio-inoculants on Growth and Yield of Soybean (Glycine max L) - Jason Masih; A. A. Kawade; V. V. Panchal (Archives of Current Research International, 2024)
An experiment entitled, "Effect of sulphur and bio-inoculants on growth and yield of soybean (Glycine Max L.)" was conducted during kharif, 2023 at new experimental cum demonstration field, SVIAg, SVVV, Indore. The field experiment was carried out in randomized block design with nine treatments. The treatments were T1- RDF (20:40:20), T2- RDF + 20 kg S ha-1, T3- RDF + 20 kg S ha-1 + Rhizobium, T4- RDF + 20 kg S ha-1+ PSB, T5- RDF + 20 kg S ha-1+ Thiobacillus, T6- RDF + 20 kg S ha-1 + Rhizobium + PSB, T7- RDF + 20 kg S ha-1 + Rhizobium + Thiobacillus, T8- RDF + 20 kg S ha-1 + Thiobacillus + PSB and T9- RDF + 20 kg S ha-1 + Rhizobium + Thiobacillus + PSB. The growth and yield attributes such as plant height, no. of leaves plant-1at 60 DAS, no. of branches plant-1, leaf area plant-1 at 60 DAS, dry matter plant-1, number of pods plant-1, pod yield plant-1, seed yield plant-1, seed yield (ha-1), straw yield (ha-1) and biological yield (ha-1) were recorded and found to be highest with the application of RDF + 20 kg S ha-1 + Rhizobium + Thiobacillus + PSB as compared to rest of the treatments. Application of RDF along with sulphur (20 kg ha-1) and seed treated with all bio-inoculants (Rhizobium, PSB and Thiobacillus) or at least one of the available bio-inoculant helps to increase soybean growth and yield of soybean.